2020
DOI: 10.1155/2020/9647072
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Cell Landscape in Different Anatomical Structures of Knee in Osteoarthritis: A Gene Expression-Based Study

Abstract: Background. Immunological mechanisms play a vital role in the pathogenesis of knee osteoarthritis (KOA). Moreover, the immune phenotype is a relevant prognostic factor in various immune-related diseases. In this study, we used CIBERSORT for deconvolution of global gene expression data to define the immune cell landscape of different structures of knee in osteoarthritis. Methods and Findings. By applying CIBERSORT, we assessed the relative proportions of immune cells in 76 samples of knee cartilage, 146 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
(60 reference statements)
1
32
0
Order By: Relevance
“…The fibrotic OA synovium contains a larger number of inflammatory M1-like macrophages compared to normal synovium, which express cell surface markers HLADR, CD63, and CD86. 213,236,241,242 The fibrotic synovium also contains a greater number of tissue repair M2-like macrophages compared to normal tissue, 236 consistent with large populations of NUPR1+ macrophages found in OA compared to inflammatory RA synovium. 238 These findings suggest that both M1-and M2-like macrophage populations contribute to OA synovial fibrosis.…”
Section: Contribution Of Macrophages and T-cells To Oa Synovial Fibrosissupporting
confidence: 63%
See 2 more Smart Citations
“…The fibrotic OA synovium contains a larger number of inflammatory M1-like macrophages compared to normal synovium, which express cell surface markers HLADR, CD63, and CD86. 213,236,241,242 The fibrotic synovium also contains a greater number of tissue repair M2-like macrophages compared to normal tissue, 236 consistent with large populations of NUPR1+ macrophages found in OA compared to inflammatory RA synovium. 238 These findings suggest that both M1-and M2-like macrophage populations contribute to OA synovial fibrosis.…”
Section: Contribution Of Macrophages and T-cells To Oa Synovial Fibrosissupporting
confidence: 63%
“…OA synovium is heterogeneous with respect to the involvement of fibrosis but synovial hyperplasia, cell proliferation, increased collagen deposition, multiple inflammatory cell infiltrates, and presence of sensory neurons are common. [234][235][236][237] Most cells associated with OA synovium are FLS and endothelial cells, with macrophages and T-cells making up most of the remaining cell types 238 (Figure 4). Recent evidence suggests that fibrosis is inversely correlated with inflammation and severity of OA and thus may represent a protective mechanism if established early.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…The high proportion of M2 macrophages in the synovial tissues has certain clinical diagnostic significance for OA (Chen et al, 2020 ), and the pro-inflammatory M1 macrophages are also increased significantly (Sun et al, 2017 ). Some studies have confirmed that macrophages play an important role in the occurrence of OA through inflammatory factors, cytokines and proteins, whether it is inflammatory or mechanical injury (Bondeson et al, 2010 ).…”
Section: Macrophage and Bone Remodeling-related Bone Diseasesmentioning
confidence: 99%
“…Pain development in OA has been shown to be well correlated with bone marrow lesion [ 1 , 45 , 46 ]. In osteoarthritic subchondral bones, the most abundant infiltrating immune cells were shown to be T cell CD8, activated mast cells and activated T cell CD4 memory, while in normal synovial samples, the most abundant infiltrating immune cells were resting mast cells, monocytes, and neutrophils [ 47 ]. BMMCs injected into the OA knee joints may function in a similar manner to the abundant activated mast cells present in the bone marrow lesion.…”
Section: Discussionmentioning
confidence: 99%